PENGARUH KUALITAS INPUT, KOMPETENSI GURU, SARANA PRASARANA SEKOLAH DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMAN PADA MATA PELAJARAN EKONOMI TAHUN AJARAN 2009/ 2010 DI SITUBONDO - Fajariana, Dewi Endah (PEDAGOGY, 2014)
This study aims to describe the effect of Input Quality, Teacher Competencies, Infrastructure Facilities for School Student Achievement in Senior High Schools in Situbondo with Learning Motivation as an intervening variable. This research was conducted in Senior High Schools in Situbondo to sample as many as 78 people. Data were collected with a questionnaire instrument and documentation. The data analysis technique used was path analysis. The results can be described briefly as follows: 1) perceived quality of inputs that significantly influence students learning achievement. 2) the competence of teachers is significant effect on student achievement. 3) school infrastructure significant effect on learning achievement. 4) motivation to study no significant effect on learning achievement.